The Return to a University Education in Great Britain - Nigel C. O'Leary; Peter J. Sloane (Institute for the Study of Labor (IZA), 2004)
In this paper, we estimate the rate of return to first degrees, masters degrees and PhDs in Britain using data from the Labour Force Survey. We estimate returns to broad subject groups and more narrowly defined disciplines, distinguishing returns by gender and attempting to control for variations in student quality across disciplines. The results reveal considerable heterogeneity in returns to particular degree programmes and by gender, which have important policy implications for charging students for the costs of their education.
Keywords: I2; J0; J3; 330; education; wages; Studium; Akademische Berufe; Bildungsertrag; Qualifikation; Geschlecht; Studienfinanzierung; Schätzung; Grossbritannien